Cultural Aspect of Basic Level English Text-Books in Nepal: Grade 6–8 - Timsina, Lok Nath (ILAM इलम, 2025)
English is mainly taught as a second or third language from pre-primary level to higher levels in Nepal. While teaching and learning any language, cultural aspect of it is inseparable and it is learned and taught as either the native culture or the target one or both. The main objective of this article is to explore how the cultural aspects are incorporated in the English text books used in community schools particularly the basic level in Nepal. To study the cultural aspects of language, I have reviewed the basic level curriculum, English text books and studied some literature related to language and culture. From the study, I have found that the major information related to both native and foreign cultures are mentioned in these textbooks. However, there is no equal treatment of them and some major cultures are highly emphasized but others are not. I recommend that the important native and foreign cultures that are lacking in these textbooks should be incorporated.